2017
DOI: 10.3389/fmicb.2017.00805
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Enhances the Efficacy of Low-Dose Antibiotic Treatment against Polymicrobial Sepsis in Mice and Clinical Isolates of ESKAPE Pathogens

Abstract: Treatment of multidrug resistant bacterial infections has been a great challenge globally. Previous studies including our study have highlighted the use of celecoxib, a non-steroidal anti-inflammatory drug in combination with antibiotic has decreased the minimal inhibitory concentration to limit Staphylococcus aureus infection. However, the efficacy of this combinatorial treatment against various pathogenic bacteria is not determined. Therefore, we have evaluated the potential use of celecoxib in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…SIRT1/Akt/NF-κB signaling can play an anti-inflammatory role in asthma, while SIRT1/HIF-1α signaling exhibits a pro-inflammatory effect ( 62 ). In addition, SIRT1/TAK1 and SIRT1/Bax pathways are implicated in tuberculosis ( 63 ), SIRT1/COX-2 signaling is involved in the development of bacterial pneumonia ( 64 ), and SIRT1/MAPK signaling is important in regulating lung cancer progression ( 65 ) ( Fig. 3 ).…”
Section: Downstream Pathways and Mechanisms Through Hmgb1mentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1/Akt/NF-κB signaling can play an anti-inflammatory role in asthma, while SIRT1/HIF-1α signaling exhibits a pro-inflammatory effect ( 62 ). In addition, SIRT1/TAK1 and SIRT1/Bax pathways are implicated in tuberculosis ( 63 ), SIRT1/COX-2 signaling is involved in the development of bacterial pneumonia ( 64 ), and SIRT1/MAPK signaling is important in regulating lung cancer progression ( 65 ) ( Fig. 3 ).…”
Section: Downstream Pathways and Mechanisms Through Hmgb1mentioning
confidence: 99%
“…Recent studies have shown that SIRT1 plays an important role in infection and inflammation ( 107 108 ). Previous in vivo and in vitro studies have demonstrated that celecoxib, a non-antibiotic agent, induced SIRT1 expression, which controlled the expressions of COX-2 and NF-κB, thus causing decreased expressions of pro-inflammatory cytokines ( 64 ). Similar effects were shown in a study on the effect of the SRT3025 compound (a SIRT1 activator) in treating pneumococcal pneumonia.…”
Section: Multitasking Roles In Respiratory Diseasesmentioning
confidence: 99%
“…Other examples include the use of a combination of cephalosporin antibiotic with diazabicyclooctane (a non-β-lactamase inhibitor) to restore susceptibility of extended-spectrum β-lactamases (ESBLs) producing E. coli and K. pneumoniae strains 8. In another approach, combination of ampicillin with a cyclooxygenase-2 (COX-2) inhibitor (eg, celecoxib) was shown to be effective in improving antibiotic efficiency in vitro against several ampicillin-resistant Gram-negative bacterial pathogens, highlighting the utility of using small molecule adjuvants to improve antibiotic activity or overcoming antibiotic resistance 10. Thus, this approach provides a platform to screen untapped chemical space in combination with different antibiotics and thereby expands the scope of antibiotic discovery.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated the inhibitory effect of ginsenoside Rh1 on HMGB1-mediated sepsis response ( 25 ). In addition, celecoxib combined with low-dose antibiotics in treating sepsis in mice can significantly reduce the bacterial load and inflammatory markers in different organs of mice ( 26 ).…”
Section: Resultsmentioning
confidence: 99%